2022
DOI: 10.1155/2022/7281120
|View full text |Cite
|
Sign up to set email alerts
|

MRGBP: A New Factor for Diagnosis and Prediction of Head and Neck Squamous Cell Carcinoma

Abstract: MRG-binding protein (MRGBP) is a transcription factor widely involved in physiological and pathological processes. Many studies have discussed the relationship between the expression level of MRGBP and the prognosis of various malignant tumours. However, the role and clinicopathological significance of MRGBP in head and neck squamous cell carcinoma (HNSC) are unclear. In this study, the Wilcoxon signed-rank test and logistic regression were used to analyze the relationship between clinical characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Multiple studies have explored the relationship between MRGBP expression levels and the prognosis of various malignant tumors. MRGBP amplification is frequently observed in numerous cancer types, including lung ( 38 ), head and neck squamous cell carcinoma ( 39 ), prostate ( 40 ), and pancreatic cancers ( 41 ). Huang’s research revealed a correlation between elevated MRGBP expression, cancer advancement, diminished survival rates, and heightened levels of immune infiltration in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have explored the relationship between MRGBP expression levels and the prognosis of various malignant tumors. MRGBP amplification is frequently observed in numerous cancer types, including lung ( 38 ), head and neck squamous cell carcinoma ( 39 ), prostate ( 40 ), and pancreatic cancers ( 41 ). Huang’s research revealed a correlation between elevated MRGBP expression, cancer advancement, diminished survival rates, and heightened levels of immune infiltration in HCC.…”
Section: Discussionmentioning
confidence: 99%